The Influence of Practicum Facilities and Infrastructure on Student Learning Interest in Mechanical Engineering Education Corrosion Course - Romadhoni, Novriando; Wadirin, Wadirin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of practicum facilities and infrastructure on student learning interest in the Corrosion course in the Mechanical Engineering Education Study Program. The method used is a quantitative method with a correlational approach. The sampling technique uses purposive sampling, with a total of 50 respondents from the class of 2022. The results of data analysis using the Pearson Product Moment correlation test showed a significance value (Sig. 2-tailed) of 0.001, which is smaller than the significance level of 0.05. Thus, an alternative hypothesis is accepted. These results show that there is a significant influence between practicum facilities and infrastructure on student learning interest in the Corrosion course in the Mechanical Engineering Education Study Program. The results of this study show that the availability and quality of practicum infrastructure facilities contribute positively to increasing student learning interest, so the institution needs to pay attention to the management and development of practicum facilities so that the learning process is more optimal.